The Effect of Aging on the Microstructure, Precipitation Response, and Fatigue Behaviour in an Al-Li-Cu Alloy - J. Fragomeni; R. Wheeler; K. V. Jata (Engineering Transactions, 2005)
The interrelationships between precipitate characteristics and mechanical properties of an Al-Li-Cu alloy was quantified. The microstructure, precipitation response, and fatigue crack growth rates in the Al-Li-Cu alloy AF/C458 were studied following single and duplex aging treatments for varying aging times on specimens that were given a six percent stretch after solution heat treatment. Aging response was studied using hardness and compression yield strength measurements. Quantitative transmission electron microscopy methods were used to characterize average size, volume fraction, number density, and interparticle spacing of strengthening precipitates, $δ^′$ (Al$_3$Li) and T$_1$ (Al$_2$CuLi). Strength and fatigue crack growth rates for select heat treatments were obtained and were related to the precipitate microstructure and yield strength data.